(untitled) (Bangladesh Journal of Medical Science, 2015)
Hydatid cysts are commonly present in liver. Cardiac hydatid cysts are very rare and represent less than 2% of all cases of hydatidosis. They can occur as widespread infection or as an isolated event. We present here a case with multiple lung hydatid cysts and a single cardiac hydatid cyst involving the apical antero-interventricular septum. A brief overview of disease and the investigations to establish the diagnosis is discussed here with introduction. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.393-395